Pengembangan Media Permainan Ilmu Pengetahuan Alam untuk Meningkatkan Minat dan Hasil Belajar MI/ SD di Gunung Kidul Jogjakarta - Daluti Delimanugari (FONDATIA, 2018)
This research is to know the development procedure of IPA game media for class IV MI / SD, to know the quality or feasibility of IPA game media for MI / SD students based on media expert and material expert, and to know the result of IPA game media development in increasing interest and learning result for fourth grade student MI Muhammadiyah Jalakan and SD Muhammadiyah Bogor in Gunungkidul. This type of research is Research and Development (R & D). Development procedures include potentials and problems, planning, drafting of products, design validation, design revisions, limited field trials, revisions of limited field trial results, broad field trials, and final product revisions. The results of the research are: 1) The game media in question is the game of Petir Pelangi and Monopoli IPA which is a game form in which there are IPA materials specially in Chapter Change of Earth Appearance and Celestial Material for class IV made by using Paint program, and equipped with auxiliary tools. 2) The results of validation of media experts and material experts indicate that the game of Petir Pelangi and Monopoli IPA is feasible or better used as media of learning media. This is based on the score score of Petir Pelangi game and Monopoli IPA respectively reaching an average of 4.3 in very good category, and 4.08 in good category. 3) In limited field trials and extensive field trials of rainbow lightning games and IPA monopolies can only increase consecutive learning interest by 6.55 with a standard gain of 0.41 in the medium category and 4, 64 with a standard gain of 0.27 in the low category. Whereas for the average of the students' learning outcomes on the limited field test and the wide field test of both game media can increase 12.77 with the standard gain of 0.31 in the medium category and 13.4 with the standard gain of 0.33 at medium category